Evaluation of mRNA Expression Profile of ABCG2/BCRP in Childhood Acute Lymphoblastic Leukemia - M Entezar-e-Ghaem; S Rahgozar; AR Moafi; J Moshtaghian; A Esmaeli; M Abedi; F Montazeri (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2013)
Introduction: Multidrug resistance (MDR) is the main obstacle against treatment of acute lymphoblastic leukemia (ALL). ATP-binding cassette transporters function is mentioned as one of the most effective factors on MDR development. Though, there are many evidences on interference of ABCG2/BCRP, one of the outstanding members of this superfamly, in MDR occurrence, the expression effect of this gene on blasts of ALL patients is unknown yet. Methods: In this study, we used Real-Time PCR technique in order to investigate the relative expression of ABCG2/BCRP mRNA in 1-17 year old children with ALL. Peripheral or bone marrow blood samples from 28 new case leukemic and 15 control children were investigated with cooperation of Seyyedo-Shohada hospital in Isfahan,. Minimal Residual Disease (MRD) was evaluated as quality of patient response to chemotherapy. Results: Profile of ABCG2/BCRP mRNA expression did not have any significant difference in new case ALL patients in comparison with control children. On the other hand, comparison of two groups of MRD+ and MRD- patients showed no difference in ABCG2/BCRP expression level. The level of ABCG2 expression was not associated with immunophenotype of ALL or known prognosis factors for this type of leukemia. Conclusion: Results of this study showed no effect of ABCG2/BCRP expression level on MDR development in ALL. Accordingly, clinical value of ABCG2/BCRP expression profile determination was rejected as the prognosis value for childhood ALL in our geographical area.